Komunikasi Politik Ditinjau dari Perspektif Ilmu Komunikasi, Ilmu Politik dan Komunikasi Islam - Erwin Jusuf Thaib (Farabi, 2019)
This article discusses political communication from three perspectives, namely the perspective of communication science, political science, and Islamic communication. The study in this article was carried out by descriptive analysis with the relevant literacy study approach. The results of this study indicate that from the perspective of communication science, political communication is seen from two aspects, namely the mechanistic communication aspect which is based on the Lasswell's theory, namely communicators convey messages to certain audiences through a medium with certain effects. The second aspect is symbolic interaction that rests on Mead's theory which views that every politician or political group will put forward a distinctive attribute as a symbol of his or her identity in a positive communication process. In a political science perspective, political communication is a vehicle that can be used to communicate political messages whose ultimate goal is the attainment of power in its various dimensions. Political communication can be played by politicians who have the goal of gaining certain power, or it can be played by professionals in which they skillfully connect political interests with their target audiences. Political communication in the perspective of Islamic communication emphasizes ethical political communication practices. This communication model is built based on Hefni’s theory which states that Islamic communication is a communication built on Islamic principles that have the spirit of peace, hospitality and safety. On this basis, the political communication model that is built is ethical political communication that is far from the practice of political communication which attacks and overthrows each other.